Crosstalk Regulation Between Bacterial Chromosome Replication and Chromosome Partitioning - Marczynski, Gregory T.; Petit, Kenny; Patel, Priya (Frontiers in Microbiology, 2019)
Despite much effort, the bacterial cell cycle has proved difficult to study and understand. Bacteria do not conform to the standard eukaryotic model of sequential cell cycle phases. Instead for example, bacteria overlap their phases of chromosome replication and chromosome partitioning. In “eukaryotic terms,” bacteria simultaneously perform “S-phase” and “mitosis” whose coordination is absolutely required for rapid growth and survival. In this review we focus on the signaling “crosstalk”, meaning the signalling mechanisms that advantageously commit bacteria to start both chromosome replication and chromosome partitioning. After briefly reviewing the molecular mechanisms of replication and partitioning, we highlight the crosstalk research from Bacillus subtilis, Vibrio cholerae and Caulobacter crescentus. As the initiator of chromosome replication, DnaA also mediates crosstalk in each of these model bacteria but not always in the same way. We next focus on the C. crescentus cell cycle and describe how it is revealing novel crosstalk mechanisms. Recent experiments show that the novel nucleoid associated protein GapR has a special role(s) in starting and separating the replicating chromosomes so that upon asymmetric cell division the new chromosomes acquire different fates in C. crescentus’s distinct replicating and non-replicating cell types. The C. crescentus PopZ protein forms a special cell-pole organizing matrix that anchors the chromosomes through their centromere-like DNA sequences near the origin of replication. We also describe how PopZ anchors and interacts with serval key cell cycle regulators thereby providing an organized subcellular environment for more novel crosstalk mechanisms.